Social Well-Being in the Hungarian Metropolitan Regions: An Empirical Application Of The Stiglitz Report - Márton Berki; Levente Halász (DETUROPE)
Based on a representative sociological survey with a sample size of 5.000 respondents carried out in 2014, this study investigates the social well-being of people living in the nine largest Hungarian cities and their metropolitan regions, in comparison with survey results from 2005. In the analysis, particular attention has been paid to the Stiglitz Report’s recommendations, to the multi-dimensional nature of social well-being, as well as to the simultaneous consideration of its objective and subjective factors. In the case of the Hungarian metropolitan regions, the eight dimensions of social well-being identified in the Stiglitz Report are explored: (1) material living standards (income, consumption and wealth), (2) health, (3) education, (4) personal activities including work, (5) political voice and governance, (6) social connections and relationships, (7) environment (present and future conditions), and (8) insecurity (of an economic as well as a physical nature). The empirical analysis revealed that the former core–periphery downward slope of metropolitan regions has clearly changed over the past ten years; whereas city centres are still in a favourable position, and the urban outskirts are getting more and more fragmented, suburban zones have undergone significant restructuring. As a result, developed and underdeveloped suburbs have seen an equalisation in terms of social well-being since 2005.